Kolaborasi Role Playing Berbantu Media Zoom sebagai Upaya Peningkatan Hasil Belajar Siswa - Edy Suryanto; Kardoyo Kardoyo; Jarot Tri Bowo Santoso; Hertaty Tiawan Anita (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2023)
Abstract: Technological developments have encouraged active and creative learning involving technology. Learning in vocational schools such as SMK is highly recommended, in line with the high adoption of technology in the world of work. This research was structured to improve student learning outcomes in Office Automation and Governance (OAG) competency skills, especially in subjects, especially Public Relations Automation and Management. Low student learning outcomes indicate the need for improvement in learning. This research is a Classroom Action Research (PTK) with two cycles with data collection through post-test and pre-test and involving 36 students of SMK 1 Pelaihari. This study aims to describe the increased learning outcomes with the role-playing method assisted by media zoom. The results of the study found that there was an increase in the completeness of student learning outcomes in cycle I by 72%, and in cycle II, the completeness of student learning outcomes reached 92%, so there was an intervention in learning in the form of applying the role-playing method assisted by zoom media to improve learning outcomes better students. These findings indicate that collaborative learning methods assisted by certain media can improve student performance as measured by learning outcomes.Keywords:Learning Outcomes, Role Playing Method, Media Zoom, Innovative Learning, Class Action Research Abstrak: Perkembangan teknologi telah mendorong pembelajaran yang aktif dan kreatif dengan melibatkan teknologi. Pembelajaran di sekolah vokasi seperti SMK sangat dianjurkan, seiring dengan tingginya adopsi teknologi di dunia kerja. Penelitian ini disusun untuk meningkatkan hasil belajar siswa kompetensi keahlian Otomasi Perkantoran dan Tata Kelola (OTKP) khususnya pada mata pelajaran khususnya Otomasi dan Tata Kelola Humas. Rendahnya hasil belajar siswa mengindikasikan perlunya perbaikan pembelajaran. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) dengan dua siklus dengan pengumpulan data melalui post-test dan pre-test dan melibatkan 36 siswa SMK 1 Pelaihari. Penelitian ini bertujuan untuk mendeskripsikan peningkatan hasil belajar dengan metode bermain peran berbantuan media zoom. Hasil penelitian menemukan bahwa terjadi peningkatan ketuntasan hasil belajar siswa pada siklus I sebesar 72% dan pada siklus II ketuntasan hasil belajar siswa mencapai 92% sehingga dengan demikian adanya intervensi dalam pemeblajaran berupa penerapan metode bermain peran (role playing) berbantuan media zoom dapat meningkatkan hasil belajar siswa yang lebih baik. Temuan ini mengindikasikan bahwa kolaborasi metode pembelajaran dengan berbantu media tertentu dapat meningkatkan kinerja siswa yang diukur melalui hasil belajar.Kata Kunci:Hasil Belajar, Metode Role Playing, Media Zoom, Pembelajaran Inovatif, Penelitian Tindakan Kelas